2010
DOI: 10.1055/s-0030-1249362
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Large-for-Gestational-Age Infants of Type 1 Diabetic Women: Morbidity and Abdominal Growth

Abstract: We sought to examine neonatal morbidity in four groups of offspring (asymmetric large for gestational age [LGA], symmetric LGA, asymmetric non-LGA, symmetric non-LGA) exposed in utero to maternal type 1 diabetes, and the association between rate of fetal abdominal circumference growth and asymmetric LGA. We performed a secondary analysis of 302 singleton pregnancies. Neonatal morbidity (respiratory distress syndrome, polycythemia, hypoglycemia, hyperbilirubinemia, acidosis, and composite morbidity [any of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…have shown that increasing maternal body mass index (BMI) is associated with increasing abdominal and intrahepatocellular lipid content in the neonatal offspring, measured by magnetic resonance spectroscopy. In fetal life, accelerated growth of the abdominal circumference (AC) is a predictor of asymmetric growth and neonatal morbidity . Moreover, Ruckinger et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have shown that increasing maternal body mass index (BMI) is associated with increasing abdominal and intrahepatocellular lipid content in the neonatal offspring, measured by magnetic resonance spectroscopy. In fetal life, accelerated growth of the abdominal circumference (AC) is a predictor of asymmetric growth and neonatal morbidity . Moreover, Ruckinger et al .…”
Section: Introductionmentioning
confidence: 99%
“…In fetal life, accelerated growth of the abdominal circumference (AC) is a predictor of asymmetric growth and neonatal morbidity. 25 Moreover, Ruckinger et al 17 have shown that BMI at 5 years was associated with the abdominal diameter of the fetus, measured in utero by abdominal ultrasound at 33 and 37 weeks of gestation and in childhood. Current AC has been shown to be an independent predictor of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Growth patterns of the AC throughout pregnancy have been shown to be altered for women with diabetes compared with normal controls 32 with AC measurements showing increased growth rate in large for gestational age (LGA) infants 4 33 , 34 Symmetry of the AC and HC measurements is also important with fetuses of diabetic mothers having an increased AC/HC ratio 32 . LGA infants with increased AC/HC ratio have a higher risk of neonatal morbidity and should be identified prior to delivery 34 .…”
Section: Discussionmentioning
confidence: 99%
“…, 33 , 34 Symmetry of the AC and HC measurements is also important with fetuses of diabetic mothers having an increased AC/HC ratio 32 . LGA infants with increased AC/HC ratio have a higher risk of neonatal morbidity and should be identified prior to delivery 34 . Rather than relying on the EFW as a standalone result, the AC and its ratio to the HC can provide extra information to women when counselling regarding delivery and risks of adverse outcomes such as shoulder dystocia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation